My friend says $\displaystyle -x^2-x+6 = (-x+2)(x+3)$ But I said its $\displaystyle -x^2-x+6 = (x+2)(x-3)$ Which one of us is right?
Follow Math Help Forum on Facebook and Google+
Originally Posted by nerdzor My friend says $\displaystyle -x^2-x+6 = (-x+2)(x+3)$ But I said its $\displaystyle -x^2-x+6 = (x+2)(x-3)$ Which one of us is right? Your friend is correct. $\displaystyle - x^2 - x + 6 = - (x^2 + x - 6) = - (x + 3)(x - 2) $ or $\displaystyle (x + 3)(2 - x) $ or $\displaystyle (-x-3)(x - 2) $
you could have expanded both to see which was correct. note that in your form you had two positive x's. this means that when we multiply them, they will yield a positive x^2, which is not what you want. one must be positive and the other negative...
View Tag Cloud